Women Lecturers’ Leadership Aspiration: A Mediation-Moderation Approach Based on Role Congruity and Self-Determination Theory - Prastiwi, Lita Era; Noermijati; Ismail, Taufiq; Badjie, Gibriel (Universitas Brawijaya, Indonesia, 2025)
There is still a big gap in the number of women in strategic leadership roles, even in colleges and universities. There is still a big gap in the number of women in strategic leadership roles, even in colleges and universities. This disparity highlights the necessity of comprehending the factors that influence the leadership ambitions of women lecturers among women academics, who continue to encounter patriarchal obstacles and the glass ceiling phenomenon. This study seeks to examine the impact of a Supportive Organizational Culture on the Leadership Aspirations of Women Lecturers, with Motivation to Lead serving as a mediator and Family Support acting as a moderator. The study employed an explanatory quantitative methodology, focusing on women lecturers at Brawijaya University who held at least the academic rank of Lecturer. The results of the study indicate that a Supportive Organizational Culture positively influences Women Lecturers' Leadership Aspiration and their Motivation to Lead. Motivation to Lead positively influences aspirations and functions as a partial mediator between Supportive Organizational Culture and Women Lecturers' Leadership Aspiration. Family Support has been proven to be the most important factor that negatively influences this relationship. This shows that Family Support functions as a buffer, so that organizational support becomes most effective in increasing leadership aspirations, especially for women who face inadequate family support. Theoretically, this study combines Role Congruity Theory and Self-Determination Theory. Practically, the findings of this study assist universities in formulating supportive strategies to increase motivation and leadership aspirations among women lecturers.